URGENSI PERJANJIAN PRANIKAH SEBAGAI KESEPAKATAN AWAL SUATU PERKAWINAN DAN AKIBAT HUKUM BAGI AHLI WARIS - Andreas Andrie Djatmiko; Gisela Anantasia; R. Soebolo (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2024)
Abstract A marriage agreement (prenup) is a form of agreement made between one party and another party before holding a wedding ceremony to validate the two as husband and wife. Household issues related to property are closely related to marriage agreements (pre-nuptials). The existence of a marriage agreement (pre-nup) is intended to avoid wealth inequality in household relationships. The aim of this research is to study, analyze and provide a general view to the public regarding marriage (pre-nup) agreements. The research method used is qualitative research through a case study approach using legislation as regulations and also processing data through cases that have occurred as research references. The function and benefits of marriage agreements (pre-nuptials) as a guideline that regulates the rights and obligations of husband and wife regarding the future of the family, whether regarding children's education, business, etc. residence, etc. as long as it does not conflict with law and morality. Protect family members from the threat of domestic violence.